PENGARUH KUANTITAS HAFALAN AL-QUR’AN DAN KECERDASAN SPIRITUAL TERHADAP PRESTASI AKADEMIK PESERTA DIDIK KELAS XI MIPA DI SMA MUHAMMADIYAH JAYAPURA - Musdalifah Musdalifah; Siti Rokhmah; Miftahul Huda (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The Senior High School of Muhammadiyah conducts the program of memorizing holy Qur’an adn other program to improve the student’s achievement. The objectives of this research are to: to analyze the big quantity influence of holy Qur’an memorization and spiritual intelligence on academic achievement grade XI MIPA in Muhammadiyah Senior High School Jayapura. To reach the objectives above, all date are collected by questionnaire method and documentation then analyzed by product moment, analyzed by product moment, analyzed and analyzed double correlation. Of 62 respondents, the results show that, the score of fscore is 22.826 by the ftable score is 3.25, so the score of fscore>ftable or 22.826>3.25, and significant level 0.000<0.05. There is a significant influence between the quantity of memorizing the Qur’an and spiritual intellegence on the academic achiavement of student in class XI MIPA In Muhammadiyah Senior High School Jayapura.